Aktivitas Antioksidan Ekstrak Air dan Etanol 70% Daun Sirih Hijau (Piper betle L.) dan Sirih Merah (Piper cf. fragile Benth.) dengan Metode Peredaman Radikal Bebas DPPH - DIANA SERLAHWATY; SETYORINI SUGIASTUTI; RIZKA CHANDRA NINGRUM (Fakultas Farmasi Universitas Pancasila, 2011)
Green betle leaf (Piper betle L.) and red betle leaf (Piper cf. fragile Benth.) were empirically used for treatment such as anti-microbial, anti-diabetic, antiseptic and resolve nosebleeds and have antioxidant activity. Phytochemical screening and antioxidant activity test have been carried out on (water and ethanol 70%) extracts of both green and red betle leaf. Phytochemical screening showed that both water and ethanol 70% extracts of both green and red betle leaf contain secondary metabolite compounds, flavonoid, alkaloid, tannin, steroid and triterpenoid, the presence of which may produce the antioxidant activity. The DPPH free radical inhibition method showed that antioxidant activity of water extract of both green betle and red betle (IC50) were 36.02 μg/mL and 60.35 μg/mL, whereas the antioxidant activity of 70% ethanol extract (IC50) were 10.59 μg/mL and 28.05 μg/mL, respectively. The highest antioxidant activity was in 70% ethanol extract of green betle (IC50 = 10.59 μg/mL), but was lower than the vitamin C (IC50 = 7.39 μg/mL) or quercetin (IC50 = 2.89 μg/mL) as positive controls. The statistical tests using twowaysanalysis of variance followed by Tukey test showed that there are significant differences between the green and red betle’s, and between water and ethanol 70% extratcs as indicated by the P value < α (α = 0.05).